2020
DOI: 10.1007/s11356-020-10627-0
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to formaldehyde, lifetime cancer probability, and hazard quotient in pathology lab employees in Iran: a quantitative risk assessment

Abstract: Formaldehyde is a colorless and highly irritating substance that is used as a preservative and chemical fixative in tissue processing in pathological laboratories. Formaldehyde is mutagenic and is classified by the IARC as the definitive carcinogen (A1 group). This cross-sectional descriptive-analytical study was performed to determine the respiratory exposure of 60 employees of pathology labs with formaldehyde and to estimate carcinogenic and non-carcinogenic risk in Iran in 2018-2019. Occupational exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Recently, Costa et al ( 2019 ) reported an average FA level of 0.38 ppm (i.e. 0.47 mg/m 3 ) in hospital anatomy-pathology laboratories in Portugal, while Jalali et al ( 2021 ) measured even higher concentrations (0.64 mg/m 3 ) in Iranian pathology wards (Costa et al 2019 ; Jalali et al 2021 ). In Italy, Scarselli et al ( 2017 ) reported a general average value of 0.49 mg/m 3 (i.e., 0.40 ppm) for workers employed in hospital activities (Scarselli et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Costa et al ( 2019 ) reported an average FA level of 0.38 ppm (i.e. 0.47 mg/m 3 ) in hospital anatomy-pathology laboratories in Portugal, while Jalali et al ( 2021 ) measured even higher concentrations (0.64 mg/m 3 ) in Iranian pathology wards (Costa et al 2019 ; Jalali et al 2021 ). In Italy, Scarselli et al ( 2017 ) reported a general average value of 0.49 mg/m 3 (i.e., 0.40 ppm) for workers employed in hospital activities (Scarselli et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, very few studies concerned the health sector, or the agri-food industry, where FA is used as a preservative. That is quite surprising, considering that there is much research about the occupational exposure to FA in pathological anatomy settings and sector rooms [ 61 , 62 , 63 ] that stress the needing for adequate preventive measures for workers [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a few studies, exposure to formaldehyde was monitored in pathology laboratory staff through personal and stationary air sampling [45][46][47], and in one study exposure to formaldehyde was assessed by personal air sampling of plastic product workers to estimate their cancer risk [48].…”
Section: Exposure Monitoring Studies Including Cancer Risk Predictionsmentioning
confidence: 99%